Preventing workplace incivility, lateral violence and bullying between nurses A narrative literature review. - Bambi, Stefano; Guazzini, Andrea; De Felippis, Christian; Lucchini, Alberto; Rasero, Laura (Acta Biomedica Atenei Parmensis, 2017)
Introduction: according to available literature workplace incivility, lateral violence and bullying among nurses are widely diffused. Their negative consequences and the outcomes on nurses and healthcare organizations have been well described. However, real pro-active and reactive actions to manage these issues, seem to be poorly recognized and investigated. Aim: to summarize the results of international studies regarding the prevention of individual and collective reactions towards workplace incivility, lateral violence, and bullying between nurses. Methods: a narrative literature review was performed. Results: 7 original papers were included in this review. The implementation of zero tolerance policies and passive dissemination of information about these phenomena showed to be clearly ineffective. Conclusions: The limited number of evidence based studies and the typologies of interventions (mainly educational rather than team building programs and assertive communication) show inadequate effectiveness plus a lacking in the scientific evidence-based support. The need to find out innovative and “creative” solutions to face these problems has been suggested by different authors